Hyperhomocysteinemia in Patients with Parkinson’s Disease and Relationship to Vitamin B Level - Hae-Won Shin; Young Ho Sohn (Journal of Movement Disorders, 2009)
Background: Plasma homocysteine (Hcy) levels are increased in patients with Parkinson’s disease (PD) undergoing levodopa treatment. We measured the Hcy levels in PD patients and assessed the relationship between Hcy level and features of PD, cognitive function and vitamin B status. Methods: Concentrations of Hcy, vitamin B12 and folate were measured in 33 PD patients and 41 normal control individuals. Mini-mental Status Examination (MMSE) was assessed in all subjects. In PD patients, Hoehn & Yahr stage and Unified Parkinson Disease Rating Scale (UPDRS) motor scores were also examined. Results: Plasma Hcy levels were lower in PD patients than in control individuals. Hcy level was inversely correlated with vitamin B12 and folate levels in the PD group but not in control individuals. Age, symptom duration, UPDRS motor scores, MMSE score, levodopa dose and duration of treatment did not differ between patients with Hcy >14 μmol/L and those with Hcy <14 μmol/L. Conclusions: Plasma Hcy levels were increased in PD patients with levodopa treatment and were related to vitamin B level. These results indicate that vitamin supplementation may be beneficial in levodopa-treated PD patients, although hyperhomocysteinemia did not affect the motor and cognitive status of PD patients.